Wikiwijs: An unexpected journey and the lessons learned towards OER - Robert Schuwer; Karel Kreijns; Marjan Vermeulen (Open Praxis, 2014)
The Dutch Ministry of Education, Culture and Science has funded a five years program to encourage the use, creation and sharing of Open Educational Resources (OER) by teachers from various types of education. This program is known as Wikiwijs. Ultimo 2013, the program has come to an end. As some of the assumptions at the start of Wikiwijs proved to work out in unexpected ways the lessons learned could fuel the next steps in developing Wikiwijs. Besides, other national initiatives on opening up education1 may also benefit from the lessons learned reported here.